Arjunolic acid from Cyclocarya paliurus ameliorates nonalcoholic fatty liver disease in mice via activating Sirt1/AMPK, triggering autophagy and improving gut barrier function. (November 2021) - Zheng, Xian; Zhang, Xiao-Gai; Liu, Yao; Zhu, Li-Ping; Liang, Xiao-Shuang; Jiang, Hui; Shi, Gao-Feng; Zhao, Yuan-Yuan; Zhao, Zhi-Wei; Teng, Yuan; Pan, Ke; Zhang, Jian; et al.
Graphical abstract: Highlights: AA potently protects against FFA-induced steatosis and HFD-induced NAFLD. AA indirectly activates Sirt1/AMPK-modulated lipid metabolism via elevating NAD+ level. AA-triggered lipophagy partly mediates its anti-steatosis effects. AA restores the impaired small intestinal barrier function. Abstract: Arjunolic acid (AA), as the most abundant triterpenoid component in Cyclocarya paliurus (Batal) Iljinskaja, previously displayed delipidating effects in free fatty acid (FFA)-induced HepG2 steatosis cells. However, whether AA still possesses the ameliorative effects on nonalcoholic fatty liver disease (NAFLD) in normal hepatocytes and in vivo remains vacant and the detailed mechanisms are not defined. In vitro, AA dose-dependently alleviated lipid accumulation in FFA-challenged primary hepatocytes without cytotoxicity. In vivo, AA showed pleiotropic benefits, including attenuating adiposity, mitigating hepatic steatosis and inflammation, improving lipid disorders and insulin resistance, and restoring the impaired gut barrier. Mechanically, we found that AA indirectly activated Sirt1/AMPK-modulated lipid metabolism through elevating NAMPT-mediated NAD + level, and triggering autophagy, together mediating the lipid-lowering effects. Collectively, our results convey that AA can substantially mitigate NAFLD via indirectly activating Sirt1/AMPK signaling, inducing autophagy and restoring gut barrier, and will be considered as a promising candidate for NAFLD therapy.